2006
DOI: 10.4103/0019-5359.19914
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant hypersensitivity syndrome to lamotrigine confirmed by lymphocyte stimulation in vitro

Abstract: Anticonvulsant hypersensitivity syndrome (AHS) developing to lamotrigine, a non aromatic anticonvulsant, has rarely been reported. We present a two-year-old boy with refractory epilepsy on valproic acid and lamotrigine therapy who developed fever and a maculopapular itchy rash. Blood investigations detected lymphocytosis and thrombocytopenia. With a presumptive diagnosis of AHS, lamotrigine was discontinued. The fever and rash resolved over the next three days and the child was discharged on valproic acid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…It is a type of drug hypersensitivity reaction and is more likely to occur with anticonvulsants. Carbamazepine, oxcarbazepine, valproate, and LTG are some of the medications implicated and cross-reactivity is about 50-80 % (Karande et al, 2006;Kaur et al, 2002). It is more common in anticonvulsants that have an aromatic benzene ring (e.g.…”
Section: Anticonvulsant Hypersensitivity Syndromementioning
confidence: 99%
“…It is a type of drug hypersensitivity reaction and is more likely to occur with anticonvulsants. Carbamazepine, oxcarbazepine, valproate, and LTG are some of the medications implicated and cross-reactivity is about 50-80 % (Karande et al, 2006;Kaur et al, 2002). It is more common in anticonvulsants that have an aromatic benzene ring (e.g.…”
Section: Anticonvulsant Hypersensitivity Syndromementioning
confidence: 99%
“…[1][2][3][4][5][6][7] AHS has been reported with nonaromatic anticonvulsant such as valproic acid (VPA) and lamotrigine (LTG), through rare. [8][9][10] Incidence of AHS is 1/1000-1/10,000 exposures [1,2] with a mortality rate of about 10%. We report a case of severe AHS secondary to injudicious combination of carbamazepine, LTG and VPA.…”
Section: A Nticonvulsant Hypersensitivity Syndrome (Ahs)mentioning
confidence: 99%
“…Less frequent are erythema multiforme and the life-threatening syndromes of drug hypersensitivity syndrome, Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). [50,[102][103][104] The total number of lamotrigine-related deaths from rash was reported at ten in 1999, with an estimated worldwide exposure of >950 000 at that time. [102] In 1999, data pooled from 1233 children revealed that 13% developed rash, with 1% considered serious.…”
Section: Skinmentioning
confidence: 99%